Effect of WEDM Machining Parameter on the MMC: A Review - Ashwin Ghaysundar; Mahendra J. Sable; Dilip M. Patel; Asmita A. Bagade; Shriram Shastri Chavali (International Journal of Fracture Mechanics and Damage Science, 2024)
Recent area of manufacturing is highly focus on good accuracy and a complex shapes are mechanized by the advanced machining operation. The wire electrical discharge machining (WEDM) have the ability to produce the complex shapes with having high accuracy. The WEDM is non-contact type machining operation and is used for metal materials as well as Metal Matrix Composites (MMCs), ceramics composites those have many application in vast areas such as defence, aircraft, automobile sector, medical equipment’s, agriculture machines, etc. As the requirement of metal properties such as light weight, good wear resistance, low density, high strength which can be possible due to combinations of two or more materials and this materials called as Metal matrix composites. The Aluminium is widely used as a base metal in MMCs along with varying reinforcement particles such as B4C, Al2O3, TiO2, ZrO2, SiC. The most of the researchers are studied on the WEDM parameters, process modelling, electrode materials, dielectric medium, etc. The considerable input parameter is the focusing area for improved Material Removal Rate, Surface Roughness and Kerf-width of composite. For a more thorough comprehension of the research conducted in this field, the diversity of studies must be categorized. This study analyzes the processing of MMCs, including the approaches taken, the results and a summary of the review. The future directions of the same field's study are also discussed in the paper.
Keywords: AlMMC; Composites; Reinforcement; WEDM